Fibrin coating of polymer vascular graft does not reduce its thromboresistance - E. A. Velikanova; T. V. Glushkova; T. N. Akentyeva; V. G. Matveeva; M. Yu. Khanova; E. O. Krivkina; Yu. A. Kudryavtseva; L. V. Antonova (Фундаментальная и клиническая медицина)
Aim. To evaluate biocompatibility along with adhesion and aggregation of platelets on the surface of uncoated and fibrin-coated poly(3-hydroxybutyrate- co-3-hydroxyvalerate)/poly(ε-caprolactone) (PHBV/PCL) small-diameter vascular grafts.Materials and Methods. 4 mm diameter grafts were fabricated by electrospinning from PHBV/ PCL (1:2) blend dissolved in 1,1,1,3,3,3-hexafluoro- 2-propanol. Inner wall of the grafts was produced using co-electrospinning of the polymer blend and collagen type I (5 mg/mL) from two different syringes. Fibrinogen was obtained from the blood of healthy donors by a cryoprecipitation procedure. Sterile polymer scaffolds were impregnated into a fibrinogen solution and immersed in a thrombin/calcium chloride blend for polymerization. To assess the biocompatibility of the grafts, primary human coronary artery endothelial cells were seeded on the luminal surface and counted under a fluorescence microscope after nuclear staining. Hemocompatibility was tested by incubation of the grafts with human platelet-rich plasma. Platelet aggregation was assessed using a platelet aggregation analyser. Surface morphology, platelet adhesion and activation were evaluated by scanning electron microscopy.Results. Fibrin coating promoted cell adhesion and proliferation and improved the graft biocompatibility as evidenced by a higher number of endothelial cells. Fibrin coating did not increase platelet aggregation, adhesion, and activation and therefore did not reduce the thromboresistance of vascular graft.Conclusion. The fibrin modification of polymer grafts from PHBV/PCL blend and collagen type I improves the surface biocompatibility and does not reduce its thromboresistance.